Impact of thermal stress during incubation on gene expression in embryonic muscle of Peking ducks (Anasplatyrhynchos domestica). (October 2015) - Liu, Hehe; Liu, Junying; Yan, Xiping; Li, Qingqing; Zhao, Yangmei; Wang, Yan; Zhang, Rongping; Wang, Guosong; Wang, Haohan; Li, Xinxin; Yang, Chao; Li, Liang; et al.
Abstract: Changes in temperature will influence poultry embryonic muscle development. However, little is known about the changes in molecular processes impacted by incubation temperature in avians. In this study, we investigated the effects of increasing the incubation temperature by 1 °C from day 11–20 on the embryonic and posthatch skeletal muscle development of the Peking duck, and identified the differentially expressed genes using RNA-seq of leg muscle tissues. The results showed that altering the incubation temperature had immediate and long-lasting effects on phenotypic changes in the embryonic and post-hatching muscle development. It was shown that expression levels of total 1370 genes were altered in muscle tissues by the thermal treatments. The gene ontology (GO) analyses indicated that cellular processes including metabolism, cell cycle, catalytic activity, and enzyme regulatory activity may have involved in the muscle mass impacted by thermal manipulation. TGF-beta and insulin pathways as two classical muscle development related pathways may also involve in regulating muscle mass. These data may be helpful for understanding the physiological and biochemical processes of muscle development under environmental treatments in embryonic avians. Highlights: We study the mechanism of thermal hatching shaping phenotypic changes of duck muscle. Transcriptome basis are illustrated in duck muscle tissues by thermal treatment. Expressions of 1370 genes are altered in muscle tissues because of thermal hatching. TGF-beta and insulin pathways might involve in muscle mass under thermal hatching.